Energy evaluation of sludge in domestic wastewater treatment plants - Lima - Estrada Alarcón, Juan Edmundo (2021)
The wastewater treatment plants in general (WWTP), give as a final result, sludge, which represents approximately 2% of the treated wastewater. In the city of Lima, with increasing population growth, the sludge produced will also be greater and therefore greater environmental pollution will be considered. One of the ways to eliminate them is the energy assessment, that is, calculating the calorific value of the sludge and comparing it with other solid fuels. The work that we present consists of carrying out a chemical, biological, percentage of humidity and fixed carbon analysis of the sludge sample from the WWTP - Ventanilla, finally the calorific value was calculated by the Gouthal method, resulting in (PC = 21667.68J / kg) for the Ventanilla WWTP, then we compare it with other solid fuels such as anthracite (PC 27907.2kJ / kg) and lignite (PC = 9108.57 kJ / kg), making it acceptable to use sludge for this purpose as an alternative to extraction of fossil materials.